Counseling for Children: Implementation of Savings at Elementary School Level at UPTD SDN 1 Sumbon, Kroya District, Indramayu Regency - Ibah Mahbubah (Konsultan Jurnal Ilmiah Indonesia, 2025)
Saving is an activity of setting aside part of the income or money owned to be stored and used in the future. The main purpose of saving is to prepare for unexpected needs or circumstances, plan for major purchases in the future, or achieve long-term financial goals. The purpose of this community service is to find out counseling for Children: Implementation of Saving at Elementary School Level at UPTD SDN 1 Sumbon, Kroya District, Indramayu Regency and specifically aims to Build savings habits from an early age, financial education, and encourage independence and prevent consumptive behavior. Counseling methods for implementing savings habits at elementary school level must be as interesting as possible, as well as interactive and in accordance with the level of understanding of the students. Methods that can be used. Using short lectures with simple language and attractive visuals. Involving students in discussions and questions and answers to ensure they understand the concept of saving, and using pre-test and post-test questions. To find out how far the ability is in understanding the material that has been delivered to the students in delivering counseling on the implementation of saving. The result of this activity is that the savings implementation counseling program at SDN 1 Sumbon was successfully implemented and received a positive response from all parties involved. Through this program, students at SDN 1 Sumbon began to understand the importance of saving and showed enthusiasm in practicing it. This activity not only provides financial education but also encourages students to form savings habits from an early age, which is expected to be a strong foundation for their financial management in the future.